Linear atrophoderma of Moulin: case report of a rare disease - Preema Sinha; Afreen Ayub; Manoj Gopal Madakshira; Juhi Sharma (Pigment International)
Linear atrophoderma of Moulin is a rare, acquired, mostly unilateral entity often presenting with hyperpigmented and atrophic band-like skin lesions that follow the lines of Blaschko. There is a considerable amount of overlap among disorders presenting along the lines of Blaschko. In this report, we discuss one such rare case along with its differential diagnosis.